The Existence of the Noken System in Simultaneous Elections in Pisugi District, Jayawijaya Regency - Noor Rahmad; Eren Arif Budiman (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
The aim of this study is to examine the existence of the noken electoral system in the 2019 elections in Pisugi District, Jayawijaya Regency. This study will further analyze the status of the noken electoral system within the national legal framework. The study employs an empirical legal method, which involves observing actual conditions within the community. The novelty of this research lies in the fact that indigenous communities must preserve the existence of the Noken electoral system, and the government must issue policies in the form of written regulations within the national legal system so that the Noken electoral system can become a democratic identity for indigenous communities in the mountainous regions of Papua. The results of the study found that there is a necessity to urge the Constitutional Court to ratify the Noken Electoral System, which is a cultural heritage of indigenous communities that must be preserved and protected. When the Constitutional Court sets aside written prohibitions to uphold justice for indigenous communities still living in the mountainous regions, its philosophical principles are also reflected. The conclusion of this study is that the government must issue written regulations regarding the Noken electoral system to serve as the foundation of the national legal system. Thus, by establishing written regulations regarding the Noken system, it will serve as a model for other regions in implementing electoral systems in accordance with their local wisdom.